Tracking the Role of Education in Preserving National Identity: Maritime Aspects in the History Subject at Senior High School in Indonesia - Singgih Tri Sulistiyono (Journal of Maritime Studies and National Integration, 2017)
One of the most important objectives of this article is analyse wether or not the idea of the Indonesian identity as a maritime nation is instructed at school in the form of teaching materials. In this respect the history subject at senior high school bocomes the focus of the study. The history subject strategically can be benefitted as the medium of strengthening the Indonesian naitonal identity as a maritime nation. This matter is very important to be studied considering the fact that untill now the issue of national identity of Indonesian nation is still to be debated wether or not Indonesia will be developed to be maritime state or conversely to be agrarian state.  But many Indonesian believe that their ancestors were maritime people. And they confident that only the people who built the country based on thier identity could be a great nation. This article argues that although the maritime history of the great potential in the process of identity formation of Indonesia as a maritime nation and has the potential to strengthen national integration, but aspects of maritime history has not taught proportionally in Indonesian history textbooks.